2015
DOI: 10.1080/00102202.2014.1002836
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Lifted Jet Flames in a Heated Coflow Using an Optimized Eddy Dissipation Concept Model

Abstract: Moderate or Intense Low oxygen Dilution (MILD) combustion has been established as a combustion regime with improved thermal efficiency and decreased pollutant emissions, including NO x and soot. MILD combustion has been the subject of numerous experimental studies, and presents a challenge for computational modelling due to the strong turbulence-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
81
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 45 publications
9
81
2
Order By: Relevance
“…Fig. 4c shows the Re à from the modified local coefficients, indicating values in the range 3-5 in the ignition region, in agreement with the modified EDC model recently proposed by Evans et al [29]. The distribution of C c (Fig.…”
Section: Determination Of Edc Coefficientssupporting
confidence: 78%
See 2 more Smart Citations
“…Fig. 4c shows the Re à from the modified local coefficients, indicating values in the range 3-5 in the ignition region, in agreement with the modified EDC model recently proposed by Evans et al [29]. The distribution of C c (Fig.…”
Section: Determination Of Edc Coefficientssupporting
confidence: 78%
“…The results were further confirmed for the analysis of the Adelaide JHC flames with methane/hydrogen mixtures [27] and with several ethylenebased blends [28]. Recently, Evans et al [29] showed that adjusting the EDC coefficients C s and C c from their default value, 0.4083 and 2.1377, to 3.0 and 1.0, respectively, results in significantly improved performance of the EDC model under MILD conditions. Although the modification of the coefficients was shown to provide improved agreement between experiments and numerical simulations, it is still necessary to identify clear guidelines for the modification of the model coefficients in the context of MILD combustion, based on the specific turbulence and chemical features of such a regime.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Since the initial publication of the EDC in the 1970s, several modifications of the EDC were proposed in literature [4][5][6][7][8], all of them claiming to improve the modeling results. In recent years, emphasis is on the extension of the EDC for Moderate or Intense Low oxygen Dilution (MILD) combustion conditions [7][8][9]. In contrast to classical turbulent combustion, MILD combustion features widely distributed reaction zones and slower reactions due to lower oxygen concentrations as well as slightly lower turbulence [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of finite-rate chemistry has a significant impact on the accuracy of turbulent, MILD flame models, 14 and may require model adjustment against experimental data for different fuels and flow conditions. [15][16][17][18] Experimentally, non-premixed MILD jet flames have shown resilience to inlet conditions. 4,19 Beyond of the MILD regime, however, the lift-off heights of autoigniting jet flames may rapidly increase or decrease with small increases in oxygen, temperature or velocity depending on small differences in initial ambient conditions.…”
mentioning
confidence: 99%